Characterization and Mitigation of Multipath for Terrestrial based Aviation Radionavigation. Issue 2 (3rd July 2018) - Schneckenburger, Nicolas; Fiebig, Uwe‐Carsten; Lo, Sherman; Enge, Per; Lilley, Robert
Abstract: In this contribution, a comprehensive overview of multipath propagation and its effects on current and future L‐band terrestrial radionavigation devices is given. The line‐of‐sight and multipath propagation between a ground station transmitter and an aircraft is characterized based on measurement data. The paper presents different methods to mitigate effects of multipath propagation and limit the resulting errors. © 2018 Institute of Navigation.